The interrelationship between pre-primary and early primary school teachers' learning in the professional community and burnout: a person-centered approach. Issue 6 (2nd November 2022) - Sullanmaa, Jenni; Pietarinen, Janne; Lipponen, Lasse; Soini, Tiina; Pyhältö, Kirsi
ABSTRACT : Teacher learning is crucial in terms of good quality education in early years and, respectively teachers' professional communities are crucial for teacher learning. The meaning of engagement in collaborative learning and resources available in professional community are emphasized in educational reforms. In this study, we explored teachers' perceptions of the resources for learning within their professional community in terms of knowledge sharing, the professional recognition received and a constructive work climate in the beginning of national curriculum reform. Individual variation in these factors was explored using latent profile analysis with a sample of 272 pre-primary and early primary school teachers. Moreover, association with the experience of burnout symptoms was examined. Three distinct profiles were identified: High fit; High recognition; Moderate knowledge sharing and fit . The results showed that teachers in the High fit profile experienced less cynicism towards the professional community. The study sheds light on the role of the recognition received from co-workers and a constructive and enabling work climate for the increased capacity to construct shared knowledge in the context of curriculum reform, and for buffering experienced cynicism.